Pengukuran Thrust dan RPM Propeller Motor Brushless pada Unmanned Aerial Vehicle (UAV) - Ahmad Alfiannor; Lilies Esthi Riyanti; Andri Kurniawan (Politeknik Penerbangan Indonesia Curug, 2022)
One of the most important components of an Unmanned Aerial Vehicle (UAV) is a brushless motor and propeller, the majority of RC component manufacturers (battery, ESC, and propeller) do not list accurate empirical performance measurements. The purpose of this study was to be able to measure thrust and RPM during the design process of the Unmanned Aerial Vehicle (UAV) in order to be able to adjust the power of the propeller to the needs of the UAV. The method used is the research and development method, which is to produce a product and test the effectiveness of the product. the test is carried out using the APC Electric 9x6 propeller by taking data at 10 different RPMs then the data will be compared with data from the results of CFD analysis as validation. The test results of the APC Electric 9x6 propeller with CFD analysis have completely agree graphs, which means that it can be concluded that the results of this test tool have been validated.